Battery separator

JP7639314B2Active Publication Date: 2025-03-05TORAY INDUSTRIES INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020201584
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-04
Publication Date
2025-03-05
Estimated Expiration
2040-12-04

AI Technical Summary

Benefits of technology

【0009】 本発明のポリオレフィン多孔質膜の少なくとも片面に耐熱性多孔層を有する電池用セパレータは、耐熱収縮性に優れ、耐熱性多孔層の脱落が少ないため、電池の安全性や歩留まりが向上する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639314000001
    Figure 0007639314000001
Patent Text Reader

Abstract

To provide a cell separator having excellent heat-resistant shrinkage and less dropout of a heat-resistant porous layer even when the heat-resistant porous layer is thin.SOLUTION: In a cell separator having a heat-resistant porous layer on at least one side of a polyolefin microporous membrane, a heat shrinkage rate of 150°C / 1h is 5% or less and the amount of the heat-resistant porous layer dropped off is 0.6 mg or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a battery separator having a heat-resistant porous layer on at least one side of a polyolefin porous membrane. [Background technology]

[0002] Thermoplastic resin porous membranes are widely used as materials for separating substances, selectively permeating them, and isolating them. For example, they are used in battery separators for lithium ion secondary batteries, nickel-hydrogen batteries, nickel-cadmium batteries, polymer batteries, and the like, separators for electric double-layer capacitors, various filters such as reverse osmosis filtration membranes, ultrafiltration membranes, and microfiltration membranes, moisture-permeable waterproof clothing, and Medical materials, etc.

[0003] In particular, as a separator for lithium ion secondary batteries, it has ion permeability due to electrolyte impregnation, excellent electrical insulation, electrolyte resistance and oxidation resistance, and can withstand abnormal battery temperature rises of 120 to 150°C. The polyimide has a pore-blocking effect that blocks current at temperatures of about 1000°C and prevents excessive heating. An olefin porous membrane is preferably used.

[0004] However, if the temperature continues to rise even after the pores are blocked for some reason, the polyolefin porous membrane This phenomenon is not limited to polyolefins. This is unavoidable above the melting point of the resin that constitutes the porous membrane.

[0005] In contrast, for polyolefin porous membranes, inorganic particles and binder resins are mainly used. By using this heat-resistant separator, the shrinkage of the polyolefin porous membrane caused by temperature rise is suppressed by the heat-resistant porous layer. It is under control. Among such separators, a separator having a heat-resistant layer formed from inorganic particles, polyvinyl alcohol (PVA), boric acid and / or an organometallic compound having PVA crosslinkability, and a water-soluble compound having a carboxyl group and / or a sulfonic acid group (Patent Document 1), and a lithium-ion battery separator formed by applying a coating liquid containing an alumina hydrate, an aqueous dispersion of a binder polymer, and an aqueous dispersant to a nonwoven fabric and drying it (Patent Document 2) have been proposed; however, these separators did not have excellent heat shrinkage resistance and little shedding of the heat-resistant porous layer even when the heat-resistant porous layer was thin. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6022227 [Patent Document 2] Patent Publication No. 2013-84367 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a separator which has excellent heat shrinkage resistance and is less susceptible to shedding of a heat-resistant porous layer even when the heat-resistant porous layer is thin. [Means for solving the problem]

[0008] The present inventors have intensively studied the prior art and have discovered a battery separator having a heat-resistant porous layer on at least one side of a polyolefin porous film, the battery separator having a heat shrinkage rate of 5% or less at 150° C. / 1 h and a falling-off amount of the heat-resistant porous layer of 0.6 mg or less. The content of inorganic particles contained in the heat-resistant porous layer is 92% by mass or more and 94.2% by mass or less, assuming that the total composition forming the heat-resistant porous layer is 100% by mass. It has been found that this problem can be solved by a battery separator characterized by: A more preferred embodiment is (1) The heat-resistant porous layer has a BET specific surface area of 11.1 m 2 / g or more, 30m 2 / g or less of precipitated barium sulfate particles. ( 2 ) The 180° peel strength of the heat-resistant porous layer is 350 N / m or more. ( 3 ) A battery separator, characterized in that the heat-resistant porous layer has a thickness of 0.5 μm or more and 4 μm or less. Effect of the Invention

[0009] The battery separator of the present invention having a heat-resistant porous layer on at least one side of the polyolefin porous membrane has excellent heat shrinkage resistance and is less susceptible to shedding of the heat-resistant porous layer, thereby improving the safety and yield of the battery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, the embodiments of the present invention will be described in detail. The present invention is not limited to the embodiment. [Polyolefin porous membrane] The thickness of the polyolefin porous membrane in the embodiment of the present invention is not particularly limited as long as it has the function of a battery separator, but is preferably 25 μm or less. More preferably, it is 3 μm or more and 20 μm or less, and even more preferably, it is 5 μm or more and 16 μm or less. When the thickness of the polyolefin porous membrane is 25 μm or less, it can achieve both practical membrane strength and pore blocking function, and the area per unit volume of the battery case is not restricted, which is suitable for increasing the capacity of the battery.

[0011] The air resistance of the polyolefin porous membrane is 30sec / 100mlAir or more, 200 sec / 100mlAir or less is preferable. More preferably, 40sec / 100mlAir ir or more, and 150sec / 100mlAir or less, and more preferably 50sec / The air resistance is 100mlAir or more and 100sec / 100mlAir or less. If it is 30sec / 100cmlAir or more, sufficient mechanical strength and insulation are obtained, reducing the possibility of short circuit during charging and discharging of the battery.If it is 200sec / 100mlAir or less, the battery's charge and discharge characteristics, especially ion permeability (charge and discharge operating voltage) and battery life (closely related to the amount of electrolyte retained) are sufficient, and the battery can fully function.

[0012] The porosity of the polyolefin porous membrane is preferably 20% or more and 70% or less. More preferably, The porosity is 30% or more and 60% or less, and more preferably 55% or less. If the ratio is more than 70%, sufficient battery charge / discharge characteristics, especially ion permeability (charge / discharge operating voltage), are not obtained. The battery has sufficient voltage (voltage) and battery life (closely related to the amount of electrolyte retained), and can fully function as a battery. It also has sufficient mechanical strength and insulation properties for charging and discharging. This reduces the possibility of a short circuit occurring during power up.

[0013] The average pore size of the polyolefin porous membrane has a large effect on the pore blocking performance. Preferably, the thickness is 1 μm or more and 1.0 μm or less. More preferably, the thickness is 0.02 μm or more and 0.5 μm or less. More preferably, the thickness is 0.03 μm or more and 0.3 μm or less. If the average pore size of the polyimide porous film is less than 0.01 μm, the organic compound may be easily generated when the heat-resistant porous layer is laminated. The pores become clogged with components, and the air resistance and electrical resistance deteriorate. If the composition is too thick, the pores will be clogged with the heat-resistant porous layer composition, and the air resistance and electrical resistance will decrease. This may result in a deterioration in resistance or a micro-short circuit, reducing the safety of the battery.

[0014] In addition, the average pore size of the polyolefin porous membrane is 0.01 μm or more and 1.0 μm or less. The anchoring effect of the composition provides sufficient heat-resistant porosity to the polyolefin porous membrane. The adhesive strength of the layers is obtained, and when the heat-resistant porous layer is laminated, the air resistance and electrical resistance are greatly improved. The average pore diameter in the present invention is not deteriorated, the response of the pore clogging phenomenon to temperature does not become slow, and the pore clogging temperature is not shifted to a higher temperature side due to the rate of temperature rise. This is a measured value obtained by the bubble point method specified in K 3832:1990.

[0015] The polyolefin resin constituting the polyolefin porous membrane is not particularly limited. However, polyethylene and polypropylene are preferred. Also, a single material or two or more different materials may be used. The material may be a mixture of olefin resins, for example a mixture of polyethylene and polypropylene, or a copolymer of different olefins. In addition to the basic characteristics, the hole blocking function cuts off the current and suppresses excessive temperature rise when the battery temperature rises abnormally. Because it has an effect.

[0016] Among them, polyethylene is particularly preferable from the viewpoint of excellent pore blocking performance. The polyolefin resin used in the present invention will be described in detail using polyethylene as an example. However, the present invention is not limited to the above.

[0017] Examples of polyethylene include ultra-high molecular weight polyethylene, high density polyethylene, and medium density polyethylene. Examples of the polymerization catalyst include high density polyethylene and low density polyethylene. There are also no particular limitations on the polymerization catalyst, and examples include Ziegler-Natta catalysts, Phillips catalysts, and metallocene catalysts. These polyethylenes are not only ethylene homopolymers, but also small amounts of other α-olefins. The α-olefin other than ethylene may be a copolymer containing propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, (Meth)acrylic acid, esters of (meth)acrylic acid, styrene, and the like are preferred.

[0018] The polyethylene may be a single substance, but must be a mixture of two or more types of polyethylene. The polyethylene mixture is preferably a mixture of two or more polyethylenes having different weight average molecular weights (Mw). Mixtures of ultra-high molecular weight polyethylene, similar high density polyethylene, and medium density polyethylene A mixture of ultra-high molecular weight polyethylene, high density polyethylene, and low density polyethylene may be used. Two or more selected from the group consisting of polyethylene, medium density polyethylene and low density polyethylene Mixtures of the above polyethylenes may also be used.

[0019] The polyolefin porous membrane must have the function of blocking the pores when the charge / discharge reaction is abnormal. Therefore, the melting point (softening point) of the resin constituting the resin is preferably 70°C or higher and 150°C or lower. More preferably, the temperature is 80° C. or higher and 140° C. or lower, and even more preferably, the temperature is 100° C. or higher and 130° C. or lower. If the melting point of the resin is between 70°C and 150°C, The hole blocking function will not be manifested and the battery will not become unusable, and the hole will not close in the event of an abnormal reaction. Safety can be ensured by realizing the blocking function.

[0020] [Heat-resistant porous layer] The heat-resistant porous layer of the present invention is provided on at least one side of the polyolefin porous membrane, and contains inorganic particles, water-soluble polymer and additives.When provided on only one side, the process of forming heat-resistant porous layer is reduced, and production cost can be reduced; when provided on both sides, the shrinkage caused by heat of polyolefin porous membrane can be suppressed from both sides, and the shrinkage caused by heat of battery separator can be more effectively reduced.

[0021] [Inorganic particles] The inorganic particles of the present invention are not particularly limited in material as long as they are electrochemically stable. Specifically, sodium oxide, potassium oxide, magnesium oxide, calcium oxide, and barium oxide. Lithium oxide, Lanthanum oxide, Cerium oxide, Strontium oxide, Vanadium oxide, SiO2 -MgO (magnesium silicate), SiO2-CaO (calcium silicate), hydrota Lucite, sodium carbonate, potassium carbonate, magnesium carbonate, calcium carbonate, barium carbonate Lithium, lanthanum carbonate, cerium carbonate, basic titanate, basic silicic titanate, basic Basic copper acetate, basic lead sulfate, layered double hydroxides (Mg-Al type, Mg-Fe type, Ni -Fe type, Li-Al type), layered double hydroxide-alumina silica gel composite, Anion adsorbents such as mites, alumina, zinc oxide, lead oxide, iron oxide, iron oxyhydroxide, hematite, bismuth oxide, tin oxide, titanium oxide, zirconium oxide, zirconium phosphate Titanium, titanium phosphate, apatite, non-basic titanates, niobates, niobium titanium Cation adsorbents such as salts of salts, zeolite, calcium sulfate, magnesium sulfate, aluminum sulfate Aluminum, Gypsum, Barium Sulfate, Alumina Trihydrate (ATH), Fumed Silica, Precipitated Silica Oxide ceramics such as silica, zirconia, and yttria, nitride ceramics such as silicon nitride, titanium nitride, and boron nitride, silicon carbide, kaolinite, talc, etc. The inorganic particles are selected from the group consisting of layered silicates such as sericite, amesite, bentonite, asbestos, diatomaceous earth, glass fiber, synthetic layered silicates such as mica or fluoromica, and zinc borate. These may be used alone or in combination of two or more. Among these, barium sulfate is particularly preferred, and precipitated barium sulfate is more preferred. Specifically, barium sulfate particles are obtained by a method of obtaining barium sulfate by adding sulfuric acid to barium carbonate or barium sulfide (sulfuric acid method), and a method of obtaining barium sulfate by adding sodium sulfate to barium chloride (mirabilite method). By using barium sulfate particles produced by a synthetic method, the volume average particle size of the inorganic particles can be controlled with high accuracy. The inorganic particles in the present invention have a BET specific surface area of ​​6.5 m 2 / g or more, 30m 2 / g or less, preferably 10m 2 / g or more, 25m 2 / g or more, more preferably 15m 2 / g or more, 20m 2 / g or less. BET specific surface area is 6.5m 2 If the BET specific surface area is less than 30 m / g, the number of contacts between the inorganic particles in the heat-resistant porous layer is reduced, making the structure of the heat-resistant porous layer fragile, making it difficult to suppress the shrinkage of the polyolefin porous film at high temperatures, or the heat-resistant porous layer may fall off during the battery manufacturing process and become mixed into the battery, resulting in a high defective rate of the battery. 2 If the BET specific surface area is greater than 6.5 m / g, the gaps between the inorganic particles are reduced, narrowing or lengthening the path of lithium ion movement in the battery, which may increase the electrical resistance. Furthermore, the inorganic particles may clog the pores of the polyolefin porous membrane, significantly reducing the performance of the battery. 2 / g or more, 30m 2 When the inorganic particles have a density of 1000 g / g or less, the heat-resistant porous layer can be prevented from falling off without impairing the heat shrinkage resistance of the heat-resistant porous layer.

[0022] [Water-soluble polymer] The water-soluble polymer used in the present invention contains at least one functional group selected from the group consisting of amino group, amide group, carbonyl group, carboxyl group, sulfonyl group, phosphoric acid group, hydroxyl group, alkyl group and halogen group in the polymer skeleton. This can exert the effect of binding inorganic particles constituting the heat-resistant porous layer together and the effect of adhering the heat-resistant porous layer to the polyolefin porous membrane. The water-soluble polymer is not particularly limited, but specifically, one or more selected from the group consisting of (meth)acrylic acid copolymer resin, polyacrylamide resin, polyvinyl alcohol resin, polyamide resin, poly(meth)aramid resin, polyethylene glycol resin and cellulose ether resin can be used, among which cellulose ether resin, polyvinyl alcohol resin and polyacrylamide resin are preferred, and cellulose ether resin and polyacrylamide resin are more preferred. These water-soluble polymers may be used alone or in combination of two or more. The water-soluble polymer referred to here is one having a heat resistance of at least 150°C or more. For example, commercially available aqueous solutions can be used. Specific examples of acrylic resins include "Jurymer" (registered trademark) AT-210, ET-410, "Aron" (registered trademark) A-104, AS-2000, and NW-7060 manufactured by Toa Gosei Co., Ltd., "Polystron" (registered trademark) 117, 705, and 1280 manufactured by Arakawa Chemical Co., Ltd., and "Kogam" (registered trademark) series manufactured by Showa Denko K.K. Examples of polyvinyl alcohol include "Kuraray Poval" (registered trademark) 3-98 and 3-88 manufactured by Kuraray Co., Ltd., and "Gosenol" (registered trademark) N-300 and GH-20 manufactured by Mitsubishi Chemical Corporation. Examples of cellulose resins include "Sunrose" (registered trademark) MAC series manufactured by Nippon Paper Industries Co., Ltd. [Other additives] The heat-resistant porous layer contains a dispersant for improving the dispersion stability of inorganic particles and a coating agent for improving coating properties. Thickeners and wetting agents for improving viscosity, and heat curing agents and crosslinking agents for improving heat resistance. A commercially available aqueous solution or dispersion can be used. Specifically, the polysol series manufactured by Showa Denko K.K. and Zeon Corporation ( "BM" series manufactured by Toa Gosei Co., Ltd., "Jurimer" (registered trademark) AT-210 manufactured by Toa Gosei Co., Ltd., ET-410, "Aron" (registered trademark) A-104, AS-2000, NW-7060, Examples of the polyvinyl alcohol include "LIOAMLUM" (registered trademark) series manufactured by Toyochem Co., Ltd., TRD202A and TRD102A manufactured by JSR Corporation, "Polystron" (registered trademark) 117, 705 and 1280 manufactured by Arakawa Chemical Co., Ltd., "Kogam" (registered trademark) series manufactured by Showa Denko K.K., and WEM-200U and WEM-3000 manufactured by Taisei Fine Chemical Co., Ltd. Examples of the polyvinyl alcohol include "Kuraray Poval" (registered trademark) 3-98 and 3-88 manufactured by Kuraray Co., Ltd., and "Gosenol" (registered trademark) N-300 and GH-20 manufactured by Mitsubishi Chemical Corporation. Some examples include: [Weight composition ratio of heat-resistant porous layer] The content of inorganic particles contained in the heat-resistant porous layer in the embodiment of the present invention is 92% by mass or more and 99% by mass or less, with the total composition forming the heat-resistant porous layer being 100% by mass. More preferably, it is 93% by mass or more and 98% by mass or less, and even more preferably, it is 94% by mass or more and 97% by mass or less. If the content of inorganic particles is less than 92% by mass, it may be difficult to suppress the shrinkage of the polyolefin porous membrane at high temperatures. If the content of inorganic particles is more than 99% by mass, the amount of composition binding the inorganic particles together is small, and therefore the heat-resistant porous layer may fall off more.

[0023] [Average thickness of heat-resistant porous layer] The average thickness of the heat-resistant porous layer in the embodiment of the present invention is preferably 0.5 μm or more and 4.0 μm or less. More preferably, it is 1.0 μm or more and 3.0 μm or less, and further preferably, it is 1.5 μm or more and 2.5 μm or less. If the thickness of the heat-resistant porous layer is smaller than 0.5 μm, it may not be possible to suppress the shrinkage of the polyolefin porous membrane due to heat. If the average thickness of the heat-resistant porous layer is larger than 4.0 μm, the distance between the positive and negative electrodes of the battery cell increases, so that the electrical resistance increases, or the proportion of the battery separator in the volume of the battery increases, so that the volumetric energy density of the battery decreases. If the average thickness of the heat-resistant porous layer is 0.5 μm or more and 4.0 μm or less, the heat-resistant porous layer can suppress the thermal shrinkage of the polyolefin porous membrane, and the electrical resistance does not increase. Furthermore, the greater the ratio of the thickness of the heat-resistant porous layer to the thickness of the battery separator, the greater the effect of the heat-resistant porous layer in suppressing the thermal shrinkage of the polyolefin porous membrane.

[0024] [Method of forming heat-resistant porous layer] The heat-resistant porous layer of the present invention can be obtained by the following steps. (a) Preparation of a coating fluid for a heat-resistant porous layer using inorganic particles, a water-soluble polymer, an additive, and a dispersion medium. (b) A step of applying the coating liquid to at least one surface or both surfaces of a polyolefin porous membrane. (c) After the coating, the dispersion medium is dried with a dryer to form a heat-resistant porous layer.

[0025] In the step (a), it is preferable to use water as the dispersion medium. As long as the dispersion stability of the coating liquid for the heat-resistant porous layer is not impaired, a hydrophilic solvent such as ethanol, isopropanol, or N-methylpyrrolidone may be mixed with water as the dispersion medium. The method for dispersing the coating liquid for the heat-resistant porous layer can be a known method. For example, a ball mill, a bead mill, a planetary ball mill, a vibration ball mill, a sand mill, a colloid mill, a roll mill, high-speed impeller dispersion, a disperser, a homogenizer, a planetary mixer and a planetary kneader, ultrasonic dispersion, mechanical stirring with a stirring blade, etc. may be mentioned. If the dispersion is insufficient, the effect of suppressing the thermal shrinkage of the polyolefin porous film by the heat-resistant porous layer may be reduced.

[0026] In the step (b), at least one or both sides of the polyolefin porous membrane are provided with a heat-resistant The method for applying the coating liquid for the porous layer can be a known method, such as a direct gravure coating method, a reverse gravure coating method, a kiss reverse gravure coating method, a direct bar coating method, a roll brush method, an air knife coating method, a Mayer bar coating method, a pipe doctor method, a blade coating method, and a die coating method, and these methods can be used alone or in combination.

[0027] The battery separator according to the embodiment of the present invention is used in nickel-metal hydride batteries, nickel-cadmium batteries, and lithium batteries, nickel-zinc batteries, silver-zinc batteries, lithium-ion secondary batteries, lithium-poly Used as a separator for secondary batteries such as lithium-sulfur batteries and lithium-ion batteries. In particular, it is preferable to use the separator as a separator for a lithium ion secondary battery. EXAMPLES

[0028] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. The measured values ​​in the examples were obtained by the following methods. In the following, Examples 1 and 5 shall be read as Reference Examples 1 and 5.

[0029] 1.BET specific surface area (m 2 / g) The measurement was performed in accordance with JIS Z 8830 (2013) using a specific surface area measuring device (Mountec Co., Ltd., fully automatic specific surface area measuring device "Macsorb" (registered trademark) HM Model-1220).

[0030] 2. Inorganic particle size (μm) The particle size of the inorganic particles was measured using a laser diffraction particle size distribution analyzer (HORIBA, Ltd., LA-960V2) in accordance with JIS Z 8825 (2013) to measure the particle size D50 (μm) at a volume-based accumulation rate of 50%. 3. Thickness (μm) The polyolefin porous membrane and the battery separator were measured using a contact type thickness meter (manufactured by Mitutoyo Corporation, "Litematic" (registered trademark)) under the conditions of a superhard spherical probe φ10.5 mm and a load of 0.15 N, and the thickness was calculated by averaging the measured values ​​at five points. Furthermore, the thickness of the heat-resistant porous layer was calculated by washing the battery separator with the same dispersion medium as the dispersion medium contained in the coating liquid for the heat-resistant porous layer, removing the heat-resistant porous layer, measuring the polyolefin porous membrane with the contact type thickness meter, and calculating the thickness according to the following formula.

[0031] Thickness of heat-resistant porous layer = Thickness of battery separator - Thickness of polyolefin porous membrane 4.Air resistance (sec / 100mlAir) The air resistance was calculated by averaging five measured values ​​using an Oken air resistance meter (manufactured by Asahi Seiko Co., Ltd., EGO-1T) in accordance with JIS P 8117. The increase in air resistance due to the heat-resistant porous layer was calculated by washing the battery separator with the same dispersion medium as that contained in the coating liquid for the heat-resistant porous layer, removing the heat-resistant porous layer, measuring the polyolefin porous membrane with the Oken air resistance meter, and calculating the air resistance using the following formula.

[0032] Increase in air permeability resistance = Air permeability resistance of battery separator - Air permeability resistance of polyolefin porous membrane 5.Heat shrinkage rate (%) The heat shrinkage rates of the battery separator in the MD direction (length direction) and TD direction (width direction) were measured by the following method. (1) Cut the battery separator into three pieces measuring 100 mm in MD x 100 mm in TD. Using a transparent glass scale (measurement accuracy 0.1 mm), measure the distance between the midpoints of the opposite sides of the battery separator as the length in MD and the length in TD, and determine the initial dimensions (mm). do. (2) The battery separator was sandwiched between two sheets of A3 size paper and placed in an oven at 150° C. for 1 hour, after which the battery separator was removed from the oven and left at room temperature for 30 minutes. (3) Using the glass scale, the distance between the midpoints of the opposite sides of the battery separator was measured again, and this was recorded as the dimension after shrinkage (mm). The measurement position at this time was the same as the position at which the initial dimension was measured. If the battery separator is in the same position and the edge is curled, unfold it and perform the measurement. From the obtained initial dimensions and dimensions after shrinkage, the heat shrinkage rates (%) in the MD and TD directions were calculated using the following formula.

[0033] Heat shrinkage rate (%) = {initial dimension (mm) - dimension after shrinkage (mm)} / initial dimension (mm) x 100 6. Amount of heat-resistant porous layer that fell off (mg) The amount of the heat-resistant porous layer that had fallen off from the battery separator was measured using a friction tester (Static / Dynamic Friction Tester TL201Tt, manufactured by Trinity Lab Co., Ltd.) according to the following method. (1) The battery separator was cut into a size of 49 mm in the TD direction × 110 mm in the MD direction, and the weight (mg) was measured using an electronic balance (measurement accuracy 0.01 mg). (2) A 50 mm x 50 mm flat contactor having a piece of single-sided adhesive cushion tape (Edge Cushion Tape TEC-50BK, manufactured by TRUSCO NAKAYAMA CORPORATION) cut to a size of 50 mm x 50 mm attached to its contact surface is fixed to the battery separator so that the cushion tape is in contact with the polyolefin porous membrane surface (in the case of a battery separator having a heat-resistant porous layer on one side) or the heat-resistant porous layer surface not to be measured (in the case of a battery separator having heat-resistant porous layers on both sides). (3) Polishing film #6000 (3M) cut to 90 mm x 220 mm TM A film abrasive (A3-2SHT, manufactured by Epson) was horizontally fixed to the sliding portion of the static and dynamic friction measuring device. (4) The polishing film is brought into contact with the heat-resistant porous layer of the battery separator fixed to the contact, and a weight of 1 kg is placed on the contact. At this time, the contact area between the polishing film and the heat-resistant porous layer is 49 mm x 50 mm. (5) After the sliding part of the static and dynamic friction tester was slid back and forth horizontally five times at a speed of 10 mm / sec and a distance of 25 mm, the battery separator was removed from the contact and its weight (mg) was measured using an electronic balance (measurement accuracy 0.01 mg). (6) From the weights (mg) of the battery separator before and after the test, the amount (mg) of the heat-resistant porous layer that fell off was calculated using the following formula.

[0034] Amount of heat-resistant porous layer that fell off (mg) = Weight of battery separator before test (mg) - Weight of battery separator after test (mg) 7. 180° peel strength of heat-resistant porous layer (N / m) The 180° peel strength of the heat-resistant porous layer was measured by the following method using a tabletop precision universal testing machine (Autograph AGS-X, manufactured by Shimadzu Corporation). (1) Cut the battery separator into a size of 25 mm in the TD direction x 100 mm in the MD direction. (2) A double-sided film tape cut to a size of 20 mm x 90 mm is applied to the polyolefin porous membrane surface of the battery separator (in the case of a battery separator having a heat-resistant porous layer on one side) or the heat-resistant porous layer surface not to be measured (in the case of a battery separator having a heat-resistant porous layer on both sides), and is pressed back and forth once using a rubber roller (manufactured by Tester Sangyo Co., Ltd., SA-1003-B tape pressing roll manual type, roll weight 2 kg, rubber hardness 80 ± 5 Hs). (3) After peeling off the release liner of the double-sided film tape, the battery separator is fixed to a metal plate of 50 mm x 150 mm. (4) A 15 mm wide single-sided adhesive tape (Nichiban Co., Ltd., "Cellotape" (registered trademark) No. 405) was applied to the heat-resistant porous layer surface of the battery separator fixed to the metal plate, and the tape was pressed back and forth five times using the rubber roller. (5) The metal plate to which the battery separator was fixed was fixed vertically to the bench-top precision universal testing machine, and within 5 minutes after the single-sided adhesive tape was applied, the single-sided adhesive tape was peeled off in a 180° direction at a speed of 100 mm / sec, and the average strength was determined from a peel distance of 40 mm to 100 mm. (6) The 180° peel strength (N / m) of the heat-resistant porous layer was calculated from the obtained peel strength and the width of the single-sided adhesive tape according to the following formula.

[0035] 180° peel strength of heat-resistant porous layer (N / m) = obtained peel strength (N) / width of single-sided adhesive tape (mm) 8. Battery defect rate [Preparation of positive electrode] An NMP solution containing 1.2 parts by mass of PVDF as a binder was added to the active material, cobalt, and 97 parts by mass of lithium oxide and 1.8 parts by mass of carbon black were added and mixed to form a cathode mixture-containing sintered body. The positive electrode mixture slurry was applied to a positive electrode collector made of aluminum foil having a thickness of 20 μm. The positive electrode layer is formed by applying the paste evenly to both sides of the electrode and drying it. Then, the paste is pressed with a roll press. The density of the positive electrode layer excluding the current collector after shrink molding is 3.6 g / cm 3 A positive electrode was prepared by the above procedure.

[0036] [Preparation of negative electrode] An aqueous solution containing 1.0 part by mass of sodium carboxymethylcellulose was added as an active material. Add 98 parts by mass of artificial graphite and mix, and add 1.0 part by mass of solids as a binder. A styrene butadiene latex containing the above-mentioned styrene was added and mixed to prepare a negative electrode mixture-containing slurry. The negative electrode mixture slurry was evenly applied to both sides of a negative electrode current collector made of copper foil with a thickness of 10 μm. The negative electrode layer was then compressed and molded using a roll press to a density of 1.45 g / cm3 after removing the current collector. 3 A negative electrode was prepared by the above procedure. [Preparation of test batteries] The above positive and negative electrodes were tabbed and each microporous membrane was used to prepare a wound body. Next, the wound body was placed in an aluminum laminate bag, and an electrolyte (1.1 mol / L, LiPF6, ethylene carbonate / ethyl methyl carbonate / diethylene carbonate = 3 / 5 / 2 (volume ratio) to which 0.5 wt% vinylene carbonate and 2 wt% fluoroethylene carbonate were added) was poured, and the bag was sealed with a vacuum sealer. Next, the bag was charged to 10% of the total capacity at a temperature of 35°C and 0.2C (C represents the current value at which the battery can be fully charged in 1 hour, and in the case of this battery, it is set to 300mA), and after storing for 12 hours, one side of the laminate was opened to vent gas, and immediately sealed with a vacuum sealer. Next, the bag was charged at a constant current and constant voltage of 0.1C, 4.35V, and a cutoff current of 0.05C at a temperature of 35°C, and then discharged at a constant current of 0.1C to 3.0V. This series of charging and discharging was the first charge and discharge. This was used as a 300mAh-class test battery.

[0037] [Battery defect rate (%)] 100 test batteries were produced, and the number of batteries with an initial charge / discharge efficiency of less than 95%, calculated according to the following formula, was taken as the defective rate.

[0038] Initial charge / discharge efficiency (%) = Initial discharge capacity / Initial charge capacity x 100 9. Battery nail penetration test A nail penetration test was carried out using five of the test batteries in accordance with SAE J2464, and the batteries were evaluated according to the following criteria. No ignition: No ignition in any of the five pieces Ignition: All 5 pieces ignited Example 1 Precipitated barium sulfate (BET specific surface area 6.5 m 2 For 100 parts by weight of 100% cellulose acetate / g, particle size D50=0.40 μm, 1.0 part by weight (active ingredient) of a polyacrylic acid-based dispersant (Aron (registered trademark) A-6114, manufactured by Toa Gosei Co., Ltd.) was prepared and added to water. Next, the entire amount of the precipitated barium sulfate was added while stirring at 700 rpm with a stirrer (Three-One Motor, manufactured by Toki Sangyo Co., Ltd.) equipped with a disperser-type blade, and the mixture was stirred at 1000 rpm for 60 minutes to obtain a mixture with a solid content of 60% by weight.

[0039] The resulting mixture was dispersed three times using a bead mill disperser (Asada Iron Works, Picomil PCM-LR) and zirconia beads with a bead diameter of 0.5 mm (Toray Industries, Inc., Treceram φ0.5 mm) under conditions of a bead filling rate of 65 volume%, a peripheral speed of 10 m / sec, and a flow rate of 16 kg / h to obtain a master batch liquid.

[0040] While stirring the obtained master batch liquid at 700 rpm with the stirrer, polyacrylamide (Polystron, manufactured by Arakawa Chemical Industries, Ltd.) as a water-soluble polymer, 2.0 parts by weight (active ingredient) of acrylic resin (Polysol AP-4735, manufactured by Showa Denko K.K.) as an additive, 0.2 parts by weight of a wetting agent (SN Wet 366, manufactured by San Nopco Ltd.), and water were added. After that, stirring was continued for 10 minutes at 700 rpm to obtain a coating liquid with a solid content of 55% by weight. The obtained slurry was applied to one side of a 12 μm-thick polyolefin porous membrane by a kiss reverse gravure method and dried at a temperature of 60° C. to obtain a battery separator with a heat-resistant porous layer having a thickness of 3 μm.

[0041] The obtained battery separator was evaluated for the increase in air permeability resistance, the heat shrinkage rate at 150°C / 1h, the amount of the heat-resistant porous layer that fell off, the 180° peel strength of the heat-resistant porous layer, the defective rate of the battery, and the nail penetration test of the battery. The results are shown in Table 1.

[0042] Example 2 The precipitated barium sulfate of Example 1 was treated with precipitated barium sulfate (BET specific surface area 11.1 m 2 A battery separator was obtained in the same manner as in Example 1, except that the powder was dispersed in a bead mill disperser 7 times, and the amount of polyacrylamide was changed to 3.0 parts by weight.

[0043] Example 3 A battery separator was obtained in the same manner as in Example 2, except that the thickness of the polyolefin porous membrane in Example 2 was changed to 20 μm.

[0044] Example 4 A battery separator was obtained in the same manner as in Example 2, except that the blending amount of polyacrylamide in Example 2 was changed to 1.5 parts by weight, and the blending amount of acrylic resin was changed to 5.0 parts by weight. Example 5 The precipitated barium sulfate of Example 1 was treated with precipitated barium sulfate (BET specific surface area 17.9 m 2 A battery separator was obtained in the same manner as in Example 1, except that the particle size (g) of the polymer was 0.15 μm, the dispersion was performed 10 times using a bead mill disperser, and the thickness of the heat-resistant porous layer was changed to 2.5 μm. Example 6 A battery separator was obtained in the same manner as in Example 2, except that the polyacrylamide in Example 2 was changed to carboxymethyl cellulose (SG-L02, manufactured by GL CHEM) and the solid content of the coating liquid was changed to 40% by weight.

[0045] Comparative Example 1 The precipitated barium sulfate of Example 1 was treated with precipitated barium sulfate (BET specific surface area 5.5 m 2 A battery separator was obtained in the same manner as in Example 1, except that the powder was changed to 0.50 μm / g and particle size D50 was changed to 0.50 μm.

[0046] Comparative Example 2 The precipitated barium sulfate of Example 2 was treated with precipitated barium sulfate (BET specific surface area 31.0 m 2 A battery separator was obtained in the same manner as in Example 2, except that the powder was dispersed in a bead mill disperser 10 times, and the amount of the acrylic resin was changed to 4.0 parts by weight.

[0047] Comparative Example 3 A battery separator was obtained in the same manner as in Example 4, except that the blending amount of the acrylic resin in Example 4 was changed to 8.0 parts by weight.

[0048] Comparative Example 4 The precipitated barium sulfate of Example 1 was mixed with eluted barium sulfate (BET specific surface area 9.1 m 2 A battery separator was obtained in the same manner as in Example 1, except that the powder was changed to 0.40 μm / g and particle size D50 was changed to 0.40 μm.

[0049] Comparative Example 5 The precipitated barium sulfate of Example 1 was mixed with alumina (BET specific surface area 6.5 m 2 A battery separator was obtained in the same manner as in Example 1, except that the dispersion speed was changed to 12 times (1 / g, particle size D50 = 0.50 µm) and the number of dispersions using the bead mill disperser was changed to 12 times.

[0050] [Table 1] [Industrial Applicability]

[0051] The separator of the present invention is preferably used in non-aqueous electrolyte batteries such as lithium ion batteries. The separator can be suitably used as a battery separator.

Claims

1. A battery separator having a heat-resistant porous layer on at least one side of a polyolefin microporous membrane, the battery separator having a 150°C / 1h heat shrinkage rate of 5% or less and a shedding amount of the heat-resistant porous layer of 0.6 mg or less, the content of inorganic particles contained in the heat-resistant porous layer being 92 mass% or more and 94.2 mass% or less, with the total composition forming the heat-resistant porous layer being 100 mass%, and the heat-resistant porous layer containing precipitated barium sulfate particles having a BET specific surface area of ​​11.1 m2 / g or more and 30 m2 / g or less.

2. A battery separator as described in claim 1, characterized in that the heat-resistant porous layer has a 180° peel strength of 350 N / m or more.

3. 3. The battery separator according to claim 1, wherein the heat-resistant porous layer has a thickness of 0.5 μm or more and 4.0 μm or less.

Citation Information

Patent Citations

  • European text processor

    JP1985022227A

  • Coating liquid, laminated porous film, and method for producing laminated porous film

    JP2013064116A

  • Coating liquid for lithium ion battery separator, and lithium ion battery separator

    JP2013084367A

  • Coating liquid, laminated porous film, and nonaqueous electrolyte secondary battery

    JP2014002953A

  • Composite barium sulfate diaphragm and preparation method therefor, and lithium-ion battery

    US20170338457A1